Fatal Balamuthia mandrillaris Encephalitis - Binoy Yohannan; Mark Feldman (Case Reports in Infectious Diseases)
Balamuthia mandrillaris is a rare cause of granulomatous meningoencephalitis associated with high mortality. We report a 69-year-old Caucasian female who presented with a 3-day history of worsening confusion and difficulty with speech. On admission, she was disoriented and had expressive dysphasia. Motor examination revealed a right arm pronator drift. Cerebellar examination showed slowing of finger-nose testing on the left. She was HIV-negative, but the absolute CD4 count was low. Neuroimaging showed three cavitary, peripherally enhancing brain lesions, involving the right frontal lobe, the left basal ganglia, and the left cerebellar hemisphere. She underwent right frontal craniotomy with removal of tan, creamy, partially liquefied necrotic material from the brain, consistent with granulomatous amoebic encephalitis on tissue staining. Immunohistochemical studies and PCR tests confirmed infection with Balamuthia mandrillaris. She was started on pentamidine, sulfadiazine, azithromycin, fluconazole, flucytosine, and miltefosine. The postoperative course was complicated by an ischemic stroke, and she died a few weeks later.